Clinical and morphological features of post-castration syndrome in women after surgical menopause - L.I. Butina; O.V. Olshevska; L.P. Shelestova; F.O. Khancha (Publishing House TRILIST, 2022)
Research objective: to assess the clinical and morphological features of the course of post-castration syndrome (PS) in women after surgical menopause. Materials and methods. The main group (with surgical menopause) consisted of 67 women aged 45 to 55 years, who underwent surgical treatment with removal of the uterus with or without appendages. 30 women with natural menopause were included in the comparison group. The assessment of morphological changes in the reproductive organs in both groups was carried out according to the results of the histological examination of reproductive organs removed during the operation, and according to the results of the pathological examination of endometrium after curettage of uterine mucosa. Results. The leading indication for surgical treatment, which led to surgical menopause, was uterine leiomyoma in 71.1% of women. Extirpation of the uterus was performed in 64.2% of patients, complete exclusion of ovarian function was observed in 68.7%. There was a deficiency of estrogen in women with surgical menopause, even before the operation, as evidenced by the presence of morphological signs of hypoestrogenism in the form of endometrial atrophy in 41.8% of them, which is 6.2 times (p < 0.001) more often compared with women with natural menopause. The morphological signs of the inflammatory process in reproductive organs in more than half of women with surgical menopause (significantly more than in women with natural menopause, p < 0.001) increase the likelihood of depletion of the ovarian hormonal function and increase the intensity of PS symptoms. This is evidenced by a significant 2.8-fold increase in women with surgical menopause in the frequency of severe PS and the median of the modified Kupperman index compared with women with natural menopause (p < 0.001). The decrease in the ovarian hormonal function in women after surgical menopause increases the frequency of ovarian cysts by 12 times compared with women with natural menopause (p < 0.001). Conclusions. It is necessary to establish the significance of the investigated clinical and morphological features observed in women with surgical menopause to predict the severity of PS in them.